(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
At the current stage, higher education is moving to a new qualitative level, reflecting innovations in the professions of "Designer" or "Architect". Hence, the need for training highly qualified specialists in these fields is growing. Given modern concepts and innovative technologies that are evident in all spheres of human life, the requirements for the level of professional training of graduates of higher educational institutions, their self-education, the ability to think independently, optimize their activities, and make unconventional, non-trivial decisions have increased. The development of relevant high-quality graphic competencies and sustainable practical skills in the process of training future creative specialists is a pressing issue. For junior students, especially in design and architecture, freehand drawing remains a fundamental skill that requires systematic development through special techniques and exercises. The main goal is to "train the hand", develop an eye, a sense of proportion and confidence in line. The development of hand graphics is inextricably linked with classical graphic disciplines, primarily the following: "Sketchy Geometry", "Geometry of Images", "Font Graphics" or "Art of Font", "Accidental Font", "Typographyk", etc. The main results of the study of methodological tools for improving the graphic capabilities of future designers and architects are reviewed by the authors using extensive research in the process of teaching first-year or second-year students graphic disciplines at the Department of Descriptive Geometry and Engineering Graphics of Odesa State Academy of Civil Engineering and Architecture (OSACEA). The research used analytical methods to summarize expert assessments of graphic and individual, in particular competitive, student works, the results of hourly observations of the performance of tasks in classroom classes provided for by the curriculum, and conclusions from a critical comparative analysis of modern publications on the methodology of teaching graphic disciplines to students with a creative profile, etc. The research results were tested in the educational process, which provides for the improvement and development of this topic in the future.